Stress Fractures: Evaluation of Three Patients and Review of the Literature - Hakan Atalar; Burcu Yanık; Onur Polat; Birkan Sonel Tur (Archives of Rheumatology, 2007)
Stress fractures occur due to mechanical overload of bones. Generally pain in the affected bone increases with activity and decreases with rest and tenderness in bone tissue is apparent on physical examination. They are frequently seen in the tibia, hip region and foot bones. In the early period, direct radiography is generally normal. Diagnosis is based on a detailed history, physical examination and advanced imaging methods. In this article, three patients with stress fractures in different anatomical regions are evaluated and similar cases in the literature are summarized. (Rheumatism 2007; 22: 31-5)